The importance of product lifetime labelling for purchase decisions: Strategic implications for corporate sustainability based on a conjoint analysis in Germany - Kathleen Jacobs; Jacob Hörisch (Business Strategy and the Environment, 2021)
This article studies the influence of product lifetime labelling on purchase decisions. Based on consumer theory of Lancaster, experimental survey data are collected from a population representative sample of 499 German consumers, using choice-based conjoint analysis. Hierarchical Bayes utility modelling suggests a substantial positive effect of product lifetime labelling on purchase decisions. However, the effect is not linear but decreasing with higher levels of product lifetime. The relative importance of the product lifetime label is found to be higher than that of the product's energy consumption or brand. Additionally, we show that the introduction of product lifetime labelling renders the positive influence of existing brands on purchase decisions less impactful. Therefore, strategic implications for companies differ substantially, depending on companies' current brand-building. Besides implications for business strategy, the study informs marketers and policymakers about the potential of product lifetime labelling to stimulate the supply of, and demand for, more durable products.
Keywords: 330; choice-based conjoint analysis; labelling; product lifetime; purchase decision; sustainable consumption